Can global health security frameworks measure One Health implementation in West Africa?: a mixed-methods study - Cham, Dalanda; Barrow, Amadou; Shah-Rohlfs, Rupal; Standley, Claire J. (BMC public health, 2024)
The 2014 outbreak of the Ebola virus disease highlighted the importance of overhauling and transforming healthcare systems in West Africa to improve the ability of individual countries to deal with infectious diseases. As part of this effort, in November 2016 the West African Health Organization (WAHO) began the process of institutionalizing the One Health (OH) approach to health security across the Economic Community of West African States (ECOWAS). The lack of clear metrics and evaluation frameworks to measure the progress of OH implementation in West Africa has been reported as a challenge. Therefore, this study sought to assess and explore whether the existing metrics of global health security frameworks can measure the successful implementation of OH activities, evaluate the progress made since 2016, and identify key areas for improvement in the region.
Gesehen am 28.04.2025